Rapid Recovery of Marine Bacterioplankton Activity after Inhibition by UV Radiation in Coastal Waters - Kaiser, E. (1997)
Laboratory and in situ experiments were performed in order to evaluate the role of UV radiation on bacterial activity. Particular attention was given to the determination of the role of UV-A and photosynthetic active radiation (PAR) and different nutrient conditions on the recovery of bacterial activity. Laboratory experiments with nearly natural radiation intensities indicated a 20 to 40% reduction from the initial level of bacterial activity after UV-B exposure for 2 to 4 h. Bacterial activity in freshly collected seawater showed a more pronounced inhibition and faster recovery than bacterial activity in aged, nutrient-depleted seawater. The results of in situ experiments with filtered water (0.8-(mu)m-pore-size filter) and natural surface solar radiation levels agreed with those of the laboratory experiments and revealed that UV-A and PAR are important for the recovery of bacterial activity and result in levels of bacterial activity that are higher than those prior to exposure to full solar radiation. Bacterioplankton exposed to full solar radiation for 3 h and subsequently incubated at different depths within the upper mixed water column showed an increase in bacterial activity with increased depth; the highest bacterial activity was detected at depths of 5.5 to 10.5 m, where the short-wavelength UV-B was already largely attenuated, but enough long wavelength UV-A and short PAR were available to allow recovery. This elevated bacterial activity following exposure to UV-B was attributed to the photolysis of dissolved organic matter (DOM) exposed to near-surface radiation and to the rapid recovery of bacteria from UV stress once they were mixed into deeper layers of the upper mixed water column, where they efficiently utilize the photolytically cleaved DOM. It is concluded that studies on the role of UV on the carbon and energy flux through the upper layer of the ocean should take into account the highly dynamic radiation conditions.